The effects of gender and education level on environmental awareness: findings from the lens of community in Seremban / Afifah Che Yusof ... [et al.] - Che Yusof, Afifah; Faizul, Aisyah; Ghazali, Marni; Md Shahid, Khairiyah; Krishnan, Devika (Universiti Teknologi MARA, Perak, 2025)
This present study examines the effects of gender and level of education on environmental awareness in Seremban, Negeri Sembilan, Malaysia. Specifically, this study aims to identify the level of environmental awareness amongst the community in Seremban and to determine the significant difference in environmental awareness based on demographic factors namely gender and level of education. Data was collected through a structured questionnaire from 231 respondents. The statistical techniques used in this study are Descriptive statistics, T-test, and One-way ANOVA to achieve the research objectives of the study. The finding of this study has revealed that the level of environmental awareness among the community in Seremban is high in which majority of the communities are aware of environmental awareness. Besides, results from independent t-tests and one–way ANOVA also have confirmed that there is a significant difference between gender and level of education towards environmental awareness.